2009
DOI: 10.1111/j.1744-7348.2008.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

A breakthrough in lupin biotechnology: prolific protocolonisation in recalcitrant white lupin (Lupinus albus) triggered by bovine serum albumin

Abstract: Six nutrient formulations were studied for their efficacy in inducing mitosis in white lupin seedling cotyledon protoplasts of which the formulations of Schä fer-Menuhr & Stü rmer (AS) and Kao (K8p) were found to be superior over the other four when supplemented with 6-benzylaminopurine and a-naphthaleneacetic acid (a-NAA). An ultrafiltration treatment of K8p increased mitotic frequency by 130% when compared with the untreated control. Medium enrichment with 0.2% bovine serum albumin (BSA) brought about a dram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
1
1
Order By: Relevance
“…In contrast, in media without additional organic ingredients, cellulose synthesis was slightly slower, but the number of wall-regenerated cells increased constantly during culture. Our results are unexpected, since in prevailing protocols for the protoplast culture of legume species, including lupins and grass pea, media rich in organic compounds are considered the most suitable for culture development (Schäfer-Menuhr & Stürmer 1987;Durieu & Ochatt 2000;Sinha & Caligari 2009). We reported previously that in cotyledonary protoplasts of yellow lupin the relatively fast cellulose resynthesis negatively affected protoplast viability (Wiszniewska et al 2012).…”
Section: Discussioncontrasting
confidence: 43%
“…In contrast, in media without additional organic ingredients, cellulose synthesis was slightly slower, but the number of wall-regenerated cells increased constantly during culture. Our results are unexpected, since in prevailing protocols for the protoplast culture of legume species, including lupins and grass pea, media rich in organic compounds are considered the most suitable for culture development (Schäfer-Menuhr & Stürmer 1987;Durieu & Ochatt 2000;Sinha & Caligari 2009). We reported previously that in cotyledonary protoplasts of yellow lupin the relatively fast cellulose resynthesis negatively affected protoplast viability (Wiszniewska et al 2012).…”
Section: Discussioncontrasting
confidence: 43%
“…Also in grass pea, the stimulation of mitoses and cluster formation was achieved after an intergeneric fusion with pea protoplasts (Durieu and Ochatt, 2000). Some recent reports have indicated that the recalcitrance in protoplast culture of several lupine species could be partially bypassed using various cultural manipulations, chemical nursing, selection of donor plants and explants (Schafer-Menuhr, 1991;Sinha and Caligari, 2009, Sonntag et al, 2009, Wiszniewska and Pindel, 2009). However, in grass pea and yellow lupine, early stages of the protoplast culture are often accompanied by disturbances in cell wall reconstitution, arrested divisions, and decreasing viability (Wiszniewska et al, 2012;Wiszniewska and Piwowarczyk, 2014).…”
Section: Introductionmentioning
confidence: 99%